The Influence of Apocalyptic Concepts on Social Life - Anvarova Muslimakhon G‘iyosiddin qizi (Indonesian Journal Publisher, 2025)
Throughout human history, apocalyptic ideas – namely conceptions of the end times, the Day of Judgment, and the ultimate destruction of the world – have consistently existed as significant religious-philosophical phenomena. These ideas have left a profound imprint not only on systems of religious belief but also on the social, political, and cultural life of societies. In particular, in the formation of new religious movements, apocalyptic thinking has played a central ideological role, encouraging collective belief, radicalization, and often violence among followers. Therefore, apocalyptic notions are regarded as objects of study that hold not only theoretical but also practical importance for contemporary sociology, religious studies, and political science. The article analyzes the influence of apocalyptic ideas on social life, with special attention to the role of eschatological and millennialist views in the emergence of new religious movements. It interprets the violent actions of apocalyptic groups – against both society and their own adherents – as a source of social instability. Furthermore, the study highlights the most dangerous aspects of apocalyptic sects, including their tendency toward isolation from society, their function as instruments of political manipulation, and their contribution to the foundation of religious extremism. The paper also provides an extensive examination of the activities of groups such as People’s Temple, Children of God, Heaven’s Gate, and Aum Shinrikyo in the late twentieth and early twenty-first centuries, focusing on mass suicides and terrorist acts. In this light, apocalyptic ideas are evaluated not merely as a religious-philosophical phenomenon but as a serious threat to social stability and global security.